* Your assessment is very important for improving the workof artificial intelligence, which forms the content of this project

# Download A Textbook of Discrete Mathematics

Survey

Document related concepts

History of the function concept wikipedia , lookup

Intuitionistic logic wikipedia , lookup

Bernard Bolzano wikipedia , lookup

Boolean satisfiability problem wikipedia , lookup

Natural deduction wikipedia , lookup

Analytic–synthetic distinction wikipedia , lookup

Laws of Form wikipedia , lookup

Meaning (philosophy of language) wikipedia , lookup

Law of thought wikipedia , lookup

Interpretation (logic) wikipedia , lookup

Accessibility relation wikipedia , lookup

Propositional calculus wikipedia , lookup

Truth-bearer wikipedia , lookup

Transcript

Module I CHAPTER 1 Introduction to Propositional Calculus 1.1 INTRODUCTION A number of words making a complete grammatical structure having a sense and meaning is called a sentence. Sentences are usually classified as declarative, exclamatory, interrogative or imperative. Proposition: A proposition or statement is a declarative sentence which is either true or false but not both. The truth or falsity of a proposition is called its truth-value. These two values ‘true’ and ‘false’ are denoted by the symbols T and F respectively. Sometimes these are also denoted by the symbols 1 and 0 respectively. Example 1: Consider the following sentences: 1. Delhi is the capital of India. 2. Kolkata is a country. 3. 5 is a prime number. 4. 2 + 3 = 4. These are propositions (or statements) because they are either true of false. Next consider the following sentences: 5. How beautiful are you? 6. Wish you a happy new year 7. x + y = z 8. Take one book. These are not propositions as they are not declarative in nature, that is, they do not declare a definite truth value T or F. Propositional Calculus is also known as statement calculus. It is the branch of mathematics that is used to describe a logical system or structure. A logical system consists of (1) a universe of propositions, (2) truth tables (as axioms) for the logical operators and (3) definitions that explain equivalence and implication of propositions. 1 2 A TEXTBOOK OF DISCRETE MATHEMATICS 1.2 FIVE BASIC CONNECTIVES The words or phrases or symbols which are used to make a proposition by two or more propositions are called logical connectives or simply connectives. There are five basic connectives called negation, conjunction, disjunction, conditional and biconditional. Negation The negation of a statement is generally formed by writing the word ‘not’ at a proper place in the statement (proposition) or by prefixing the statement with the phrase ‘It is not the case that’. If p denotes a statement then the negation of p is written as G p and read as ‘not p’. If the truth value of p is T then the truth value of G p is F. Also if the truth value of p is F then the truth value of G p is T. Table 1. Truth table for negation p Gp T F F T Example 2: Consider the statement p : Kolkata is a city. Then G p : Kolkata is not a city. or It is not the case that Kolkata is a city. Although the two statements ‘Kolkata is not a city’ and ‘It is not the case that Kolkata is a city’ are not identical, we have translated both of them by G p. The reason is that both these statements have the same meaning. Notes: (i) A given statement (proposition) in the object language is denoted by a symbol and it may correspond to several statements in English. This multiplicity happens since in a natural language one can express oneself in several manners. (ii) G p is also denoted as ∼ p, p and p′. Conjunction The conjunction of two statements (or propositions) p and q is the statement p ∧ q which is read as ‘p and q’. The statement p ∧ q has the truth value T whenever both p and q have the truth value T. Otherwise it has truth value F. Table 2. Truth table for conjunction p q p∧q T T F F T F T F T F F F Example 3: Consider the following statements p : It is raining today. q : There are 10 chairs in the room. Then p ∧ q : It is raining today and there are 10 chairs in the room. Note: Usually, in our everyday language the conjunction ‘and’ is used between two statements which have some kind of relation. Thus a statement ‘It is raining today and 1 + 1 = 2’ sounds odd, but in logic it is a perfectly acceptable statement formed from the statements ‘It is raining today’ and ‘1 + 1 = 2’. 3 INTRODUCTION TO PROPOSITIONAL CALCULUS Example 4: Translate the following statement: ‘Jack and Jill went up the hill’ into symbolic form using conjunction. Solution: Let p : Jack went up the hill, q : Jill went up the hill. Then the given statement can be written in symbolic form as p ∧ q. Disjunction The disjunction of two statements p and q is the statement p ∨ q which is read as ‘p or q’. The statement p ∨ q has the truth value F only when both p and q have the truth value F. Otherwise it has truth value T. Table 3. Truth table for disjunction p q p∨q T T F F T F T F T T T F Example 5: Consider the following statements p : I shall go to the game. q : I shall watch the game on television. Then p ∨ q : I shall go to the game or watch the game on television. Conditional proposition If p and q are any two statements (or propositions) then the statement p → q which is read as, ‘If p, then q’ is called a conditional statement (or proposition) or implication and the connective is the conditional connective. The conditional is defined by the following table: Table 4. Truth table for conditional p q p→q T T F F T F T F T F T T In this conditional statement, p is called the hypothesis or premise or antecedent and q is called the consequence or conclusion. To understand better, this connective can be looked as a conditional promise. If the promise is violated (broken), the conditional (implication) is false. Otherwise it is true. For this reason, the only circumstances under which the conditional p → q is false is when p is true and q is false. Example 6: Translate the following statement: ‘The crop will be destroyed if there is a flood’ into symbolic form using conditional connective. Solution: Let c : the crop will be destroyed; f : there is a flood. Let us rewrite the given statement as 4 A TEXTBOOK OF DISCRETE MATHEMATICS ‘If there is a flood, then the crop will be destroyed’. So, the symbolic form of the given statement is f → c. Example 7: Let p and q denote the statements: p : You drive over 70 kms per hour. q : You get a speeding ticket. Write the following statements into symbolic forms. (i) You will get a speeding ticket if you drive over 70 kms per hour. (ii) Driving over 70 kms per hour is sufficient for getting a speeding ticket. (iii) If you do not drive over 70 kms per hour then you will not get a speeding ticket. (iv) Whenever you get a speeding ticket, you drive over 70 kms per hour. Solution: (i) p → q (ii) p → q (iii) G p → G q (iv) q → p. Notes: 1. In ordinary language, it is customary to assume some kind of relationship between the antecedent and the consequent in using the conditional. But in logic, the antecedent and the consequent in a conditional statement are not required to refer to the same subject matter. For example, the statement ‘If I get sufficient money then I shall purchase a high-speed computer’ sounds reasonable. On the other hand, a statement such as ‘If I purchase a computer then this pen is red’ does not make sense in our conventional language. But according to the definition of conditional, this proposition is perfectly acceptable and has a truth-value which depends on the truthvalues of the component statements. 2. Some of the alternative terminologies used to express p → q (if p, then q) are the following: (i) p implies q (ii) p only if q (‘If p, then q’ formulation emphasizes the antecedent, whereas ‘p only if q’ formulation emphasizes the consequent. The difference is only stylistic.) (iii) q if p, or q when p. (iv) q follows from p, or q whenever p. (v) p is sufficient for q, or a sufficient condition for q is p. (vi) q is necessary for p, or a necessary condition for p is q. (vii) q is consequence of p. Converse proposition The conditional proposition q → p is called the converse proposition of p → q. Contrapositive proposition The conditional proposition G q → G p is called the contrapositive proposition of p → q. Inverse proposition The conditional preposition G p → G q is called the inverse proposition of p → q. Table 5. Truth table for four propositions p q Gp Gq Conditional p→q T T F F T F T F F F T T F T F T T F T T Converse q→p Contrapositive Gq→Gp Inverse Gp→Gq T T F T T F T T T T F T 5 INTRODUCTION TO PROPOSITIONAL CALCULUS Example 8: Consider the following statements. p : It rains; q : The crops will be grown. Conditional p → q : If it rains then the crops will be grown. Converse q → p: If the crops grow then there has been rain. Contrapositive G q → G p : If the crops do not grow then there has been no rain. Inverse G p → G q: If there is no rain then the crops will not grow. Example 9: Construct the truth table for (p → q) ∧ (q → p). Solution: p q p→q q→p (p → q) ∧ (q → p) T T F F T F T F T F T T T T F T T F F T Biconditional proposition If p and q are any two statements (propositions), then the statement p q which is read as ‘p if and only if q’ and abbreviated as ‘p iff q’ is called a biconditional statement and the connective is the biconditional connective. The truth table of p q is given by the following table: Table 6. Truth table for biconditional p q T T F F T F T F p q T F F T It may be noted that p q is true only when both p and q are true or when both p and q are false. Observe that p q is true when both the conditionals p → q and q → p are true, i.e., the truth-values of (p → q) ∧ (q → p), given in Ex. 9, are identical to the truth-values of p q defined here. p q can also be stated as p is a necessary and sufficient condition for q. Note: The notation p ↔ q is also used instead of p q. Example 10: Let p and q denote the following propositions: p : He is poor; q : He is happy. Express each of the following propositions in symbolic form using p and q. (i) To be poor is to be unhappy. (ii) He is poor if and only if he is happy. (iii) Being rich is a necessary and sufficient condition to being happy. 6 A TEXTBOOK OF DISCRETE MATHEMATICS Solution: (i) p G q q. (iii) G p 1.3 (ii) p q STATEMENT FORMULAS AND TRUTH TABLES We have already defined the connectives G , ∧, ∨, → and . We shall occasionally distinguish between two kinds of propositions (or statements) in our symbolic language. The statements which do not contain any connectives are called atomic or primary or simple statements. On the other hand, those statements which contain one or more primary statements and some connectives are known as molecular or composite or compound statements. Some of the compound statements formed by using any two statements p and q are p ∧ ( G q). G p, p ∨ q, (p ∧ q) ∨ ( G p), (p ∨ q) These compound statements are statement formulas derived from the statement variables p and q. Therefore, p and q may be called the components of these statement formulas. It is to be noted that in addition to the connectives we have also used parentheses in some cases in order to make the formula unambiguous. Our basic concern is to find the truth-value of a statement formula for each possible combination of the truth-values of the component statements. A table showing all such truth values is called the truth table of the given statement formula. Example 11: Construct the truth table for the statement formula p ∨ G q. Solution: p q Gq p∨Gq T T F F T F T F F T F T T T F T Example 12: Construct the truth table for (p ∨ q) ∨ G p. Solution: 1.4 p q p∨q Gp (p ∨ q) ∨ G p T T F F T F T F T T T F F F T T T T T T TAUTOLOGY AND CONTRADICTION Tautology: A statement formula which is true regardless of the truth values of the statements which replace the variables in it is called a universally valid formula or a logical truth or a tautology. Contradiction: A statement formula which is false regardless of the truth values of the statements which replace the variables in it is said to be a contradiction. 7 INTRODUCTION TO PROPOSITIONAL CALCULUS Contingency: A statement formula which is neither a tautology nor a contradiction is known as a contingency. Example 13: Show that p ∨ G p is a tautology and p ∧ G p is a contradiction. Solution: p Gp p∨Gp p∧Gp T F F T T T F F From the truth table it is clear that p ∨ G p is a tautology and p ∧ G p is a contradiction. (G p ∨ G q) is a Example 14: Using truth table, show that the statement formula G (p ∧ q) tautology. Solution: p q p∧q G (p ∧ q) Gp Gq T T F F T F T F T F F F F T T T F F T T F T F T G p ∨ G q G (p ∧ q) F T T T (G p ∨ G q) T T T T Here the truth values of the given formula are T for all possible truth values of p and q. Hence (G p ∨ G q) is a tautology. G (p ∧ q) Notes: (i) Obviously, the negation of a contradiction is a tautology and conversely. (ii) A statement formula which is a tautology is identically true and a formula which is a contradiction is identically false. (iii) Suppose P(p, q, ...) is a tautology. Then it does not depend upon the particular truth values of its variables p, q, ..., so we can substitute a for p, b for q, ..., for any propositions a, b, ... in the tautology P(p, q, ...) and still have a tautology P(a, b, ...). It is also true for contradiction. 1.5 EQUIVALENCE OF FORMULAS Two statement formulas A and B are equivalent provided A B is a tautology. Conversely, if A B is a tautology then A and B are equivalent. We shall represent the equivalence of two statement formulas, say A and B, by writing ‘A ⇔ B’ which is read as ‘A is equivalent to B’. Example 15: Prove that (i) (p ∨ G p) ⇔ (q ∨ G q) (ii) (p → q) ⇔ (G p ∨ q). Solution: (i) p Gp p∨Gp q Gq q∨Gq T T F F F F T T T T T T T T F F F F T T T T T T ∴ (p ∨ G p) ⇔ (q ∨ G q) since (p ∨ G p) (p ∨ G p) (q ∨ G q) is a tautology. (q ∨ G q) T T T T 8 A TEXTBOOK OF DISCRETE MATHEMATICS (ii) p q p→q Gp Gp∨q T T F F T F T F T F T T F F T T T F T T (p → q) (G p ∨ q) T T T T Observe that the truth values in the columns for p → q and G p ∨ q are identical and so the biconditional will have the truth values T. ∴ (p → q) ⇔ (G p ∨ q ). 1.6 EQUIVALENT FORMULAS OR LOGICAL EQUIVALENCES 1. (i) p ∨ p ⇔ p 2. (i) p ∨ q ⇔ q ∨ p 3. (i) p ∨ (q ∨ r) ⇔ (p ∨ q) ∨ r 4. (i) p ∨ (q ∧ r) ⇔ (p ∨ q) ∧ (p ∨ r) (ii) p ∧ (q ∨ r) ⇔ (p ∧ q) ∨ (p ∧ r) 5. p → q ⇔ G p ∨ q 7. (i) p ∨ F ⇔ p 8. (i) p ∨ T ⇔ T 9. (i) p ∨ G p ⇔ T 10. (i) p ∨ (p ∧ q) ⇔ p 11. (i) G (p ∨ q) ⇔ G p ∧ G q 12. p q ⇔ (p → q) ∧ (q → p) (ii) p ∧ p ⇔ p (ii) p ∧ q ⇔ q ∧ p (ii) p ∧ (q ∧ r) ⇔ (p ∧ q) ∧ r 6. p → q ⇔ G q → G p (ii) p ∧ T ⇔ p (ii) p ∧ F ⇔ F (ii) p ∧ G p ⇔ F (ii) p ∧ (p ∨ q) ⇔ p (ii) G (p ∧ q) ⇔ G p ∨ G q (Idempotent laws) (Commutative laws) (Associative laws) (Distributive laws) (Law of contrapositive) (Absorption laws) (De Morgan’s laws) Note: Here most of the equivalences have straight forward intuitive interpretations and all of them can be verified by constructing truth tables. Example 16: Show that (G p ∧ (G q ∧ r)) ∨ (q ∧ r) ∨ (p ∧ r) ⇔ r. Solution: (G p ∧ (G q ∧ r)) ∨ (q ∧ r) ∨ (p ∧ r) [By distributive law] ⇔ (G p ∧ (G q ∧ r)) ∨ ((q ∨ p) ∧ r) [By associative law] ⇔ ((G p ∧ G q) ∧ r) ∨ ((q ∨ p) ∧ r) [By distributive law] ⇔ ((G p ∧ G q) ∨ (q ∨ p)) ∧ r [By De Morgan’s and commutative laws] ⇔ (G (p ∨ q) ∨ (p ∨ q)) ∧ r ⇔ T ∧ r ⇔ r. (Proved) Example 17: Prove that ((p ∨ q) ∧ G (G p ∧ (G q ∨ G r))) ∨ (G p ∧ G q) ∨ (G p ∧ G r) is a tautology. Solution: Using De Morgan’s laws: G p ∧ G q ⇔ G (p ∨ q), G p ∧ G r ⇔ G (p ∨ r) ∴ (G p ∧ G q) ∨ ( G p ∧ G r) ⇔ G (p ∨ q) ∨ G (p ∨ r) INTRODUCTION TO PROPOSITIONAL CALCULUS 9 ⇔ G ((p ∨ q) ∧ (p ∨ r)) Also, G (G p ∧ (G q ∨ G r)) ⇔ G (G p ∧ G (q ∧ r)) ⇔ G (G (p ∨ (q ∧ r))) ⇔ p ∨ (q ∧ r) ⇔ (p ∨ q) ∧ (p ∨ r) [By distributive law] Therefore, the given expression becomes ((p ∨ q) ∧ (p ∨ q) ∧ (p ∨ r)) ∨ G ((p ∨ q) ∧ (p ∨ r)) ⇔ ((p ∨ q) ∧ (p ∨ r)) ∨ G ((p ∨ q) ∧ (p ∨ r)) ⇔ T Hence the given statement formula is a tautology. Example 18: Show that r s ⇔ (r ∧ s) ∨ (G r ∧ G s). Solution: r s ⇔ (r → s) ∧ (s → r). [∵ (p → q) ⇔ (G p ∨ q), see Ex. 15(ii)] ⇔ (G r ∨ s) ∧ (G s ∨ r) [By distributive law] ⇔ ((G r ∨ s) ∧ G s) ∨ (( G r ∨ s) ∧ r) [By distributive law] ⇔ ((G r ∧ G s) ∨ (s ∧ G s)) ∨ ((G r ∧ r) ∨ (s ∧ r)) [∵ p ∧ G p ⇔ F and By commutativity] ⇔ ((G r ∧ G s) ∨ F) ∨ (F ∨ (s ∧ r)) [∵ p ∨ F ⇔ p and By commutativity] ⇔ (G r ∧ G s) ∨ (s ∧ r) [By commutativity] ⇔ (r ∧ s) ∨ (G r ∧ G s) Example 19: Prove that G (p ∧ q) → (G p ∨ (G p ∨ q)) ⇔ G p ∨ q. Solution: G (p ∧ q) → (G p ∨ (G p ∨ q)) ⇔ (G (G (p ∧ q))) ∨ ( G p ∨ (G p ∨ q)) [∵ (p → q) ⇔ (G p ∨ q), see Ex. 15(ii)] ⇔ (p ∧ q) ∨ (( G p ∨ G p) ∨ q) [∵ p ∨ p ⇔ p] ⇔ (p ∧ q) ∨ ( G p ∨ q) [By associativity] ⇔ ((p ∧ q) ∨ G p) ∨ q (By distributive law) ⇔ ((p ∨ G p) ∧ (q ∨ G p)) ∨ q ⇔ (T ∧ (q ∨ G p)) ∨ q ⇔ (q ∨ G p) ∨ q (By commutative and associative laws) ⇔ G p ∨ (q ∨ q) ⇔ G p ∨ q. (Proved) q)) → q is a tautology. Example 20: Prove that (p ∧ (p Solution: p ∧ (p q) ⇔ p ∧ (p → q) ∧ (q → p) ⇔ p ∧ (G p ∨ q) ∧ (G q ∨ p) [By commutativity and associativity] ⇔ (p ∧ (p ∨ G q)) ∧ (G p ∨ q) [By absorption law] ⇔ p ∧ (G p ∨ q) [By distributive law] ⇔ (p ∧ G p) ∨ (p ∧ q) ⇔ F ∨ (p ∧ q) ⇔ p ∧ q. ∴ (p ∧ (p q)) → q ⇔ (p ∧ q) → q [∵ (a → b) ⇔ ( G a ∨ b)] ⇔ G (p ∧ q) ∨ q [By De Morgan’s law] ⇔ (G p ∨ G q) ∨ q [By associativity] ⇔ G p ∨ (G q ∨ q) ⇔ G p ∨ T ⇔ T. Hence (p ∧ (p q)) → q is a tautology. (Proved) 10 1.7 A TEXTBOOK OF DISCRETE MATHEMATICS NORMAL FORMS : DNF AND CNF It will be convenient to use the word product in place of conjunction (∧) and sum in place of disjunction (∨) in the current discussion. Elementary product: A product of the variables and their negations in a statement formula is called an elementary product. Elementary sum: A sum of the variables and their negations in a statement formula is called an elementary sum. Disjunctive normal form (DNF): A statement formula which is equivalent to a given formula and which consists of a sum of elementary products is called a disjunctive normal form (DNF) of the given formula. Example 21: Obtain disjunctive normal forms of (p ∧ q). (i) p ∧ (p → q) (ii) G (p ∨ q) Solution: [See Ex. 15(ii)] (i) p ∧ (p → q) ⇔ p ∧ ( G p ∨ q) [By distributive law] ⇔ (p ∧ G p) ∨ (p ∧ q) This is the required DNF. (p ∧ q) ⇔ (G (p ∨ q) ∧ (p ∧ q)) ∨ ((p ∨ q) ∧ G (p ∧ q)) (ii) G (p ∨ q) [Using r s ⇔ (r ∧ s) ∨ (G r ∧ G s), see Ex.18] (By De Morgan’s laws) ⇔ (G p ∧ G q ∧ p ∧ q) ∨ ((p ∨ q) ∧ (G p ∨ G q)) (By distributive law) ⇔ (G p ∧ G q ∧ p ∧ q) ∨ ((p ∨ q) ∧ G p) ∨ ((p ∨ q) ∧ G q) (p ∧ q) ∴ G (p ∨ q) ⇔ (G p ∧ G q ∧ p ∧ q) ∨ (p ∧ G p) ∨ (q ∧ G p) ∨ (p ∧ G q) ∨ (q ∧ G q) (By distributive law) This is the required DNF. Example 22: Obtain a disjunctive normal form of p → ((p → q) ∧ G ( G q ∨ G p)). Solution: p → ((p → q) ∧ G ( G q ∨ G p)) [∵ r → s ⇔ G r ∨ s] ⇔ G p ∨ ((p → q) ∧ G (G q ∨ G p)) [By De Morgan’s law] ⇔ G p ∨ ((G p ∨ q) ∧ G (G (q ∧ p))) p ∨ (( p ∨ q) ∧ (q ∧ p)) ⇔ G G p ∨ (( [By distributive law] ⇔ G G p ∧ (q ∧ p) ∨ (q ∧ (q ∧ p)) [By commutative and associative laws] ⇔ G p ∨ (p ∧ G p ∧ q) ∨ (q ∧ q ∧ p) p ∨ (F ∧ q) ∨ (q ∧ p) ⇔ G ⇔ G p ∨ F ∨ (q ∧ p) ⇔ G p ∨ (q ∧ p) This is the required DNF. Principal disjunctive normal form (PDNF): Minterm: A product (or conjunction) in which each variable or its negation, but not both, occurs only once is called a minterm. For two variables p and q, there are 22 = 4 possible minterms : p ∧ q, p ∧ G q, G p ∧ q and G p ∧ G q.